Use of nicotine replacement therapy for smoking reduction and during enforced temporary abstinence: a national survey of English smokers. - Beard, E; McNeill, A; Aveyard, P; Fidler, J; Michie, S; West, R (2011)
AIMS: To assess the prevalence of nicotine replacement therapy (NRT) use for smoking reduction (SR) and temporary abstinence (TA), the association between the two and the strength of the association between NRT use for SR or TA and socio-demographic characteristics, cigarette consumption and past quit attempts. DESIGN: Cross-sectional monthly surveys. SETTING: England. PARTICIPANTS: A total of 11, 414 smokers. MEASUREMENTS: Participants were asked (i) whether they were reducing the amount they smoked: if so, whether they used NRT; and (ii) whether they used NRT for TA. Demographic characteristics, daily cigarette consumption and whether a quit attempt had been made in the past 12 months were also assessed. FINDINGS: Of the participants, 56% were attempting SR, 14% were using NRT for SR and 14% were using NRT for TA. Use of NRT for SR and TA were highly correlated. The nicotine patch was the most commonly used form of NRT. The use of NRT for SR, compared with unassisted SR, was more common among older smokers, while the use of NRT for TA was more common among women. Cigarette consumption was higher in those using NRT for SR than those attempting SR without NRT. The use of NRT for SR and TA was associated positively with past quit attempts. CONCLUSIONS: Nicotine replacement therapy use for smoking reduction and temporary abstinence is common in England. The use of NRT for SR and TA does not appear to be associated with lower cigarette consumption relative to SR or TA without NRT, but is associated with a higher rate of past quit attempts.